Coloração de espécimes anatômicos para aplicação no processo de plastinação por meio de corantes histológicos : floxina b, safranina, fucsina fenicada e tricrômico de masson - Siqueira, Bruno Magela de Melo (2018)
The Study of Anatomy has been known for several centuries and before this, every moment has generated several repercussions in this area of biomedical sciences. Even with advancement in the technological sectors, the teaching of anatomical concepts through corpses in health courses is still essential. A more common way of preserving anatomical parts for studies is through a substance that was discovered in 1867 by German Hoffman by accident: formaldehyde, but such substance has an unpleasant odor and irritates the nasal passages and the eye region. Plastination is the newest in terms of technology for the preservation of anatomical specimens. This technique was developed by the German Dr. von Hagens in 1977 and its principles reflect in the idea of impregnating polymers (silicone, epoxy or polyester) in biological tissues, removing the fat and water present, thus increasing their durability and with aspects close to the original object. Plastination is free from toxic conservative substances, thus facilitating its role for didactic and scientific purposes. The dye is used for a better visualization of the structures in the anatomical part and thus ending with that aspect of worn, emphasizing the true color of the object. In view of the above, has developed a staining protocol in skeletal muscle tissue, applied to the Plastination technique with the following dyes: Phloxine B, Safranin, Phenicated Fuchsin and Masson's Trichrome. The interaction of the dye with the muscle tissue, fat and epithelial tissue of the samples that were used for the research was evaluated. All the dyes used in the macroscopic staining were able to show certain structures such as tendon, fascia and connective tissue inside the muscle. It was also evaluated the photodegradation of these dyes in solution. It was noticed that the dyes that obtained more satisfactory results in relation to the dyeing of the specimens were those of anionic character: Phloxine B and Masson's Trichrome, but in relation to the resistance of the dyes in light exposure, it was not possible to choose the one that obtained the best because the solutions exhibited different behaviors when exposed to light. The final protocol for the staining muscle tissues will be applied in the collection of the Life Sciences Museum of the Federal University of Espírito Santo and in the Department of Morphology of the same University.